The scientific articles on art criticism - Hedayat, M. (Canadian Center of Science and Education, 2015)
Research has been extremely involved in improving in the art criticism area. These improvements are reflected in scientific articles. This article purposed to investigate the 214 articles in art criticism to explore their main characteristics. These articles published in the Web of Science database of the Institute of Scientific Information (ISI) from the period of 1980 till 20 December 2013. Types of articles were article and review which is included in the study. The three top cited (more than 10 times citations) articles in art criticism were published in 1993 and 1999. The 214 articles mean citation rate was 0.87 (SD 2.38) times. Among the various fields, art (58.87), arts humanities other topics (28.03), both art and arts humanities other topics (5.14), both art and education and educational research (2.33), both art and history (1.40), art, arts humanities other topics and literature (1.40), both art and cultural studies (0.93), both art and philosophy (0.93), both art and literature (0.46), and both arts humanities other topics and cultural studies (0.46) were the most popular fields of research. The results showed that researches were done in the United States had highest citation which was written in English language.